Performance enhancement of relays used for next generation wireless communication networks - Saraju Prasad Padhy; Madhusmita Panda; Srinivas Sethi; Aruna Tripathy (Institute of Advanced Engineering and Science, 2021)
Relaying is one of the latest communication technologies developed for wireless networks like WiMAX, LTE Advanced and 5G Ultra Reliable Low Latency Communication (URLLC) networks to provide coverage extension as well as higher bitrates for cell edge users. Thus they are included in the design of next generation wireless communication systems to provide performance improvement in terms of coverage and capacity over their predecessors. Other promising features of this technology include easy to implement and reduction in deployment cost. The objective of this paper is to analyze both cooperative and non-cooperative relaying techniques in the Infinite Block length regime and findout the benefits of Relay implementation. A single Amplify and Forward (A&F) Relay is used for this purpose. Reduction in power requirement for Simple Relay is shown in comparison to the direct transmission, using experimental analysis with Matlab simulation. SER (Symbol error rate) is calculated at the receiver for no relay, simple Relay and Cooperative Relaying scenario to show the improvements of cooperative Relaying implementation.The performance enhancement of the Relay is then carried out using Particle Swam Optimization (PSO) optimization technique where allocation of power between Base station and Relay Node is effectively distributed for optimum performance.